PELATIHAN ALAT PEMADAM API RINGAN DAN KARUNG GONI SEBAGAI MEDIA PEMADAMAN KEBAKARAN KEPADA MAHASISWA POLIBATAM, SISWA DAN GURU SMK DI BATAM - Adhitomo Wirawan; Himawan Mochtoha; Muhammad Zainuddin; Irsutami Irsutami; Aulia Fajrin; Andre Akhnedi; Felix Russel; Vinda Yessica; Putri Ramadini; Shakila Lulu Fadillah Halim; Budiman Budiman (P3M Politeknik Negeri Malang, 2024)
Fire disaster is one of the many disasters that occur in the wider community both in the office and residential environment. This fire disaster generally occurs due to human factors such as: using electrical loads that exceed the power capacity and placing flammable items near the source of fire. This fire hazard will be easier to overcome if people know how to put out fires properly and know how to use extinguishers such as APAR (Light Fire Extinguisher) and the use of gunny sacks. APAR is generally categorized into 3 types, namely: Dry Chemical Extinguisher, Carbon Dioxide (CO2) Extinguisher, and Foam. Extinguishers containing dry chemical powder are very commonly used because they are able to extinguish almost all types of fires. The use of APAR is most likely to be used because of its portable nature, easy maintenance, and easy to use. In the community service that has been carried out at Batam State Polytechnic, a demonstration on how to extinguish fire with fire extinguisher and the use of gunny sacks was also carried out. Participants of this community service program are students, vocational school students and vocational school teachers.